2020
DOI: 10.1186/s13054-020-03275-w
|View full text |Cite
|
Sign up to set email alerts
|

Implications for post critical illness trial design: sub-phenotyping trajectories of functional recovery among sepsis survivors

Abstract: Background Patients who survive critical illness suffer from a significant physical disability. The impact of rehabilitation strategies on health-related quality of life is inconsistent, with population heterogeneity cited as one potential confounder. This secondary analysis aimed to (1) examine trajectories of functional recovery in critically ill patients to delineate sub-phenotypes and (2) to assess differences between these cohorts in both clinical characteristics and clinimetric properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 64 publications
4
38
2
Order By: Relevance
“…In our study, population with only mandatory education was an independent predictor for the occurrence of PICS. This observation is consistent with that of the previous studies, which demonstrated that population with only mandatory education was associated with physical impairment [ 49 ], mental impairment [ 55 ] and PICS [ 7 ]. Socioeconomic position is a broad term which assesses the socioeconomic status, including education level, occupation and income.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, population with only mandatory education was an independent predictor for the occurrence of PICS. This observation is consistent with that of the previous studies, which demonstrated that population with only mandatory education was associated with physical impairment [ 49 ], mental impairment [ 55 ] and PICS [ 7 ]. Socioeconomic position is a broad term which assesses the socioeconomic status, including education level, occupation and income.…”
Section: Discussionsupporting
confidence: 93%
“…The underprivileged persons often have high rates of cardiovascular disease and mortality due to tobacco smoking and less physical activity [ 55 ]. Furthermore, those who received less formal education is associated with low income, small social network to use resources for recovery, less coping ability for the rehabilitation process and less accurate recall [ 7 , 49 , 55 , 56 ]. Additionally, financial distress has a direct effect on mental status [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, population with only mandatory education was an independent predictor for the occurrence of PICS. This observation is consistent with that of the previous studies, which demonstrated that population with only mandatory education was associated with physical impairment [49], mental impairment [55], and PICS [7]. Socioeconomic position is a broad term which assesses the socioeconomic status, including education level, occupation, and income.…”
Section: Comparison To Other Studiessupporting
confidence: 92%
“…Responsiveness is the instrument's ability to detect change over time in the construct to be measured [47,48]. Responsiveness of SF-36 PCS and MCS scores to negative change or no change in Global Assessment Rating at 6 months was calculated using the effect size index [49,50]. Cohen's d effect size was used to evaluate the changes as small (0.2-0.49), moderate (0.5-0.79), and large (> 0.80) [47,51].…”
Section: Statistical Analysesmentioning
confidence: 99%